Species-specific DNA probes for the identification of Actinobacillus actinomycetemcomitans - Emanuel, Margot (Division of Medical Microbiology, 2017)
A DNA probe was developed for the identification of the periodontal pathogen, Actinobacillus actinomycetemcomitans. Chromosomal DNA was extracted from A. actinomycetemcomitans, digested with a restriction enzyme, Sau3A, ligated to plasmid DNA (pUC18) and transformed into JM109 cells to give a partial A. actinomycetemcomitans library. The library was screened using Southern blot analysis. Out of the nine inserts tested, one was found to be species specific as it did not cross-hybridise to Haemophilus aphrophilus, a closely related organism which occurs in the normal oral microflora, nor did it cross-hybridise with 7 species of Bacteroides tested. A level of detection of 104 cells or 50ng of A. actinomycetemcomitans was obtained. The probe has a length of 779bp and out of 30 restriction enzymes tested, only SspI was found to have a restriction site in the insert. The probe was tested on clinical specimens obtained from five different periodontitis patient groups and was shown to correlate with culture results in eighteen out of twenty-two cases in detecting A. actinomycetemcomitans.